Press Advertising – Varieties and Sub-Varieties. Methods of Promoting the Press - Joanna Mikosz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2016)
In the text entitled “Press advertising – varieties and sub-varieties. Methods of promoting the press”, the author discusses press advertising, which is a fast developing mass-media phenomenon. Modernity has granted press advertising a high quality of print and paper, as well as Infinite possibilities of combining various promotional forms with the press. The author argues that press advertising is one of the best ways in which a company can communicate with the market. Its advantage is, above all, a high frequency of distributing the contents and the possibility of conveying accurate advertising information in vast quantities.